Local food procurement behavior and overall diet quality among adults in Québec: results from the NutriQuébec project - Marianne Rochette; Gabrielle Rochefort; Catherine Laramée; Annie Lapointe; Simone Lemieux; Ariane Bélanger-Gravel; Sophie Desroches; Véronique Provencher; Benoît Lamarche (Nutrition Journal)
Abstract Background Consumption of locally produced foods is generally perceived as being part of a healthy dietary pattern. Accordingly, in 2020, the provincial government of Québec (Canada) promoted the purchase of local foods for economic and health benefits. The present cross-sectional study aimed to document the association between the behavior of local food procurement and overall diet quality in a sample of adults from the province of Québec. Methods Data were collected in a sample of 834 adults (86.6% females) from the NutriQuébec project, a web-based longitudinal population study that aims to document the lifestyle and eating habits of adults in Québec, Canada. Dietary intakes were measured using a validated web-based 24-h recall tool and diet quality was assessed using the Healthy Eating Food Index (HEFI-2019), which measures adherence to the 2019-Canada’s Food Guide recommendations on healthy food choices. Local food procurement behavior was measured using the Locavore-I-SF score, which assesses the frequency of short food supply chain use as well as the geographical origin of three locally produced foods. Results The Locavore-I-SF score was weakly correlated with the HEFI-2019 score (r = 0.08, p < 0.02). Positive correlations were observed for the Vegetables and fruits (r = 0.09, p = 0.005), Beverages (r = 0.08, p = 0.04) and Free sugars (r = 0.14, p < 0.001) components of the HEFI-2019. Associations between the Locavore-I-SF and the HEFI-2019 scores were found in specific subgroups of participants: males (r = 0.33, p < 0.001), participants aged between 50 and 70 years (r = 0.16, p = 0.003), participants with a greater education level (r = 0.13, p = 0.003) and higher income (r = 0.12, p = 0.02), non-vegetarian participants (r = 0.10, p = 0.008) and participants living in Census Metropolitan Areas (r = 0.11, p = 0.004). Conclusion These results suggest that the behavior of local food procurement is only weakly associated with better overall diet quality among a sample of adults from Québec, raising doubts on the relevance of promoting local food procurement as an effective public health measure for improving diet quality in Québec. Study registration number NCT04140071.